GC Insights: Consistency in pyrocartography starts with color - B. J. Hatchett (Geoscience Communication)
Fire progression maps provide operational and public information regarding wildland fire spread, size, and proximity to critical assets through time. Cartographic guidance regarding the use of color to denote the sequential nature of fire progression is limited, leading to inconsistency in fire progression maps produced for operational, research, and public applications, which potentially limits these maps' accessibility and ability to effectively communicate information. In this paper, I provide color map recommendations to facilitate consistent, intuitive, and accessible fire progression mapping.